Choking on Statutes Revisited: A History of Legislative Preemption of Common Law Regarding Child Custody - SAMPSON, JOHN J. (Family law quarterly, 2011)
This article describes in truncated form one portion of the massive expansion and extensive legislative specification of family law policies in Texas throughout the last four decades. It is a story of ever-increasing infatuation with highly detailed statutory regulation. Most of the changes, large and small, in the allocation of "parental custody and visitation," in the Texas Family Code are tracked from 1973 through 1995. The largest metropolitan areas, Dallas-Fort Worth-Arlington, San Antonio, and Houston, designate trial judges who generally specialize in family law. In much of the rest of Texas, such specialization is not common practice. Thus, experience with the typical issues varies greatly from court to court. Arguably, judges with the most contact with the subject matter would be best suited to make the choices for public policy. How that proposition works out in practice is at the heart of this essay.